Properties of regulated exocytosis in astrocytes - Zorec, Robert (Henry Stewart Talks, 2011)
Exocytosis, Exocytosis in evolution, Exocytosis in astrocytes, Development of eumetazoans, Neuromuscular junction and secretory organelles, The patch-clamp monitoring of membrane capacitance (surface area) in cultured neurones and astrocytes, Simultaneous measurements of cell swelling by monitoring cell cross section area and membrane capacitance, Astrocytes exhibit calcium-dependent regulated exocytosis, Glutamate release from astrocytes, Calcium-dependent release of peptides